Project Double Barrel: Crime Rate and Experiences of the Implementers in the Municipality of Diplahan, Zamboanga Sibugay - Precillas, Antonette F.; Pallega, Rowell B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aimed to determine the crime rate in the Municipality of Diplahan, Zamboanga Sibugay in the calendar years 2013-2015 and 2016-2018. Specifically, this study described the index and non-index crimes prior to and during the implementation of the project double barrel and whether significant differences existed on the crime profiles prior to and during the project. It also aimed to identify the experiences encountered by the imple-menters of the project under CMC 16 2. 2016. Archived data were taken from police blotters and crime statistics given by the PNP Personnel in Diplahan Police Station and employed the qualita-tive design using in-depth interview to generate and explore the experiences of the PNP Personnel and Barangay Captains before and during the implementation of the project. Thematic analysis was then applied to generate codes and themes that described the experiences of the participant-interviewees. Findings re-vealed the decrease in index crimes, which include serious of-fenses like murder, theft, and robbery, suggests an improvement in public safety. The heightened police presence and visibility likely acted as a deterrent to violent and property crimes, con-tributing to a more secure environment in public areas. There is a need for a multifaceted approach to improving law enforce-ment's effectiveness and ethical standards in addressing drug-related crimes. Integration of advanced technologies and en-hanced coordination among agencies to improve operations and monitoring capabilities and collaboration with external organi-zations focuses on rehabilitation and prevention, while inde-pendent oversight mechanisms and regular reviews are also needed to ensure accountability, transparency, and continuous improvement of policies and drug related operations. Stronger collaboration between police, local governments, NGOs, and health organizations is also necessary to reinforce community-based rehabilitation efforts and preventive measures. Providing mental health support for officers is equally important, as it im-proves their well-being, reduces burnout, and fosters ethical de-cision-making under high-pressure situations. Comprehensive training for officers is vital to prepare them for the complexities of the drug campaign, improving operational effectiveness and promoting accountability within the force.